Practices in intercultural language teaching and learning - Ennis, Michael Joseph; Riley, Catherine Elizabeth (Cambridge Scholars Publlishing, 2017)
This volume responds to the growing need for intercultural approaches to teaching and learning languages. The central premise is that the aim of intercultural language teaching and learning is to foster effective communication and effective learning in spaces between cultures in order to prepare learners for global citizenship, but that the corresponding models and methods must emerge from the bottom-up in order to meet the needs of each unique context. The book offers a collection of successful experiences rooted in praxis. It shares the activities, methods, models, and approaches which have.